Foreign Policy of Provisional Priamur Government (1921—1922): Process of Formation and Basic Ideological Attitudes - F. A. Popov; V. Z. Tsvetkov (Научный диалог)
The article is devoted to the foreign policy course of the anti-Bolshevik Provisional Priamurye Government, which controled Primorye in 1921—1922. The source base of the research was the journalism of the pro-government press (the newspapers “Slovo”, “Russian Territory”, “Bulletin of the Provisional Priamurye Government”) and archival materials. Particular attention is paid to the role of the media in substantiating the foreign policy of the Far Eastern non-socialists. It is shown that the official statements of the government (appeals, proclamations, interviews of officials) published in the press contained the foundations of the foreign policy doctrine of the White movement. In addition, it is indicated that anti-Bolshevik publicists regularly responded to foreign policy events and tried to form public opinion through newspaper articles. It is noted that the cornerstone of the program of the Provisional Priamurye Government was the thesis of the antagonism of “Russia” (personified in the white Primorye) and “Sovdepia” — RSFSR (together with the buffer Far Eastern Republic). As an example, illustrating the application of Provisional Priamurye Government ideological attitudes in practice, the sending of a delegation from the white Primorye to the Washington conference at the end of 1921 is given. The preceding press campaign, designed to substantiate the importance of the presence of the anti-Bolshevik delegation in Washington, is highlighted.